Análise de propriedades topológicas das redes biológicas integradas da Escherichia coli e da Saccharomyces cerevisiae - Andrade, Tiago Felipe [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Biological processes are complex and possess emergent properties that can not be explained or predict by reductionism methods. To overcome the limitations of reductionism, researchers have been used a group of methods known as systems biology, a new interdisciplinary eld of study aiming to understand the non-linear interactions among components embedded in biological processes. These interactions can be represented by a mathematical object called graph or network, where the elements are represented by nodes and the interactions by edges that link pair of nodes. The networks can be classi- ed according to their topologies: if node degrees follow a Poisson distribution in a given network, i.e. most nodes have approximately the same number of links, this is a random network; if node degrees follow a power-law distribution in a given network, i.e. small number of high-degree nodes and high number of low-degree nodes, this is a scale-free network. Moreover, networks can be classi ed as hierarchical or non-hierarchical. In this study, we analised Escherichia coli and Saccharomyces cerevisiae integrated molecular networks, which have protein-protein interaction, metabolic and transcriptional regulation interactions. By using computational methods, such as MathematicaR , and data collected from public databases, we calculated four topological parameters: the degree distribution P(k), the clustering coe cient C(k), the closeness centrality CC(k) and the betweenness centrality CB(k). P(k) is a function that calculates the total number of nodes with k degree connection and is used to classify the network as random or scale-free. C(k) shows if a network is hierarchical, i.e. if the clusterization coe cient depends on node degree. CC(k) is an indicator of how much a node it is in the lesse way among others some nodes of the network and the CB(k) is a pointer of how a particular node is among several ...(Complete abstract click electronic access below)

Processos biológicos são complexos e possuem propriedades emergentes que não podem ser explicadas ou previstas através do reducionismo. Para suplantar esses limites, pesquisadores têm usado um conjunto de métodos conhecido como biologia sistêmica, cujo objetivo é a compreensão das interações não-lineares entre os múltiplos componentes dos processos biológicos. Essas interações podem ser representadas por um objeto matemático chamado grafo ou rede, onde os elementos interagentes são representados por nodos e as interações por ligações que conectam pares de nodos. As redes podem ser classi cadas segundo sua topologia, podendo ser aleatórias ou livres de escala, sendo que nessa última o número de conexões de um nodo segue a lei de potência, existindo poucos nodos altamente conectados e muitos nodos com poucas ligações. Elas também são classi cadas como hierárquicas ou não, e segundo essa classi cação respeita-se uma ordem de conexão entre os nodos e seus graus de conectividade, que de ne essa hierarquia. Neste trabalho, analisamos as redes moleculares integradas da bactéria Escherichia coli e da levedura Saccharomyces cerevisiae, que incluem interações físicas entre proteínas, interações metabólicas e interações de regulação transcricional. Através de ferramentas computacionais, como MathematicaR , e dos dados obtidos de bancos de dados públicos, realizamos a medição de quatro parâmetros topológicos: a distribuição de conectividades P(k), o coe ciente de agrupamento médio de todos os nodos com k conexões C(k), o grau de proximidade CC(k) e o grau de intermediação CB(k). O P(k) é uma função que calcula o número total de nodos com grau k de conexão e serve para classi car a rede como aleatória ou livre de escala. O C(k) mostra se uma rede é hierárquica, isto é, se o agrupamento dos nodos depende da conectividade dos mesmos. O Cc(k) ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Fisica medica; Bioinformática